Baseflow estimation for catchments in the Loess Plateau, China. (1st March 2019) - Zhang, Junlong; Song, Jinxi; Cheng, Lei; Zheng, Hongxing; Wang, Yetang; Huai, Baojuan; Sun, Weijun; Qi, Shanzhong; Zhao, Panpan; Wang, Yuqi; Li, Qi
Abstract: Baseflow is the portion of streamflow that originates from groundwater. It is pivotal to groundwater supply as well as the interactions between groundwater and surface water. In the Loess Plateau of China, the baseflow plays a fundamental role in sustaining the aquatic ecosystem. Rational estimation of baseflow is of critical importance for understanding the functioning of the groundwater system and informing management of regional water resources. In this study, a two-well parameterised digital filter was used to separate baseflow from observed daily total streamflow on the Weihe River Basin. Two parameters (maximum baseflow index ( BFI max ) and the recession constant) of this filter were estimated using UKIH and a recession analysis with physical meaning, respectively. The results show that the baseflow index increased from the upstream to downstream (0.27–0.32) of the Weihe River, and the baseflow of the river is summer dominant. In general, the baseflow has been increasing gradually owing to the implementation of soil conservation measures. This study provides an understanding of baseflow response to seasonal variability and water environmental management in basin scale. Highlights: The baseflow in the loess regional catchment with the spatial attributes. Baseflow shows a gradually increasing trend from upstream to downstream in the Weihe River Basin. The baseflow of this river is dominated by summer baseflow.